Simulation of CO2 rich natural Gas pilot plant carbon dioxide absorption column at elevated pressure using equilibrium and rate based method - Marik Singh, S.K. (Springer Verlag, 2017)
This paper reports a steady state model for CO2 removal using MEA solvent that operates at elevated pressure and the behaviour that affects the performance of CO2 absorption process. All the input for the simulation has been acquired from the experimental work using pilot plant which is located at Universiti Teknologi PETRONAS (UTP). Steady state simulation has been demonstrated using Aspen Plus utilizing both equilibrium and rate based approaches. Modifications for the equilibrium based method has been done to ensure similarity between rate based and equilibrium based simulation. Since Aspen Dynamic does not support rate based model, adjustment made to the equilibrium model will enable the model to be used for future studies which involves dynamic and control study. The most relevant input parameters of the equilibrium model are methodically varied and the influence of that variation on the simulation results based on CO2 removal percentage was monitored. The evaluation has been conducted to observe the percentage of CO2 removal by setting the Murphree efficiency and varying number of stages of absorber unit. © Springer Nature Singapore Pte Ltd. 2017.